2002
DOI: 10.1038/nrc706
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistance in cancer: role of ATP–dependent transporters

Abstract: Chemotherapeutics are the most effective treatment for metastatic tumours. However, the ability of cancer cells to become simultaneously resistant to different drugs--a trait known as multidrug resistance--remains a significant impediment to successful chemotherapy. Three decades of multidrug-resistance research have identified a myriad of ways in which cancer cells can elude chemotherapy, and it has become apparent that resistance exists against every effective drug, even our newest agents. Therefore, the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
4,115
4
48

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 4,960 publications
(4,205 citation statements)
references
References 133 publications
38
4,115
4
48
Order By: Relevance
“…The hydrophilic drugs usually can enter into cells by piggybacking on transporters that are responsible for transporting nutrients and specific agents into cells through endocytosis, but it may fail to accumulate inside MDR cancer cells instead of the efflux effect 27. For instance, Shen et al found that cisplatin‐resistant cancer cells showed pleiotropic defects, associated with reduced plasma membrane protein, which finally reduced accumulation of drugs and became cross‐resistance to anticancer drugs,28 while there was no obvious overexpression of energy‐dependent efflux transporters.…”
Section: Mechanisms Of Cancer Multidrug Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…The hydrophilic drugs usually can enter into cells by piggybacking on transporters that are responsible for transporting nutrients and specific agents into cells through endocytosis, but it may fail to accumulate inside MDR cancer cells instead of the efflux effect 27. For instance, Shen et al found that cisplatin‐resistant cancer cells showed pleiotropic defects, associated with reduced plasma membrane protein, which finally reduced accumulation of drugs and became cross‐resistance to anticancer drugs,28 while there was no obvious overexpression of energy‐dependent efflux transporters.…”
Section: Mechanisms Of Cancer Multidrug Resistancementioning
confidence: 99%
“…Even worse, the recurrent tumors often produce a population of MDR cancer cells, in order to make it more malignant, that spread quickly and are resistant to radiotherapy or previously treated drugs. CSCs have been reported to express a high level of drug efflux proteins, such as P‐gp, MRP1, and BCRP, to help CSCs avoid damages from cytotoxic drugs and resist to chemotherapy 2, 27, 53. Furthermore, CSCs also demonstrated active DNA‐repair and detoxification capacity, for example, the expression of Aldehyde dehydrogenases1 (ALDH1), a molecular metabolic detoxification enzyme for catalyzing oxidation of aldehyde formation in alcohol metabolism,54 has been frequently elevated as investigated in some CSC cell lines to activate tumor recurrence 55.…”
Section: Mechanisms Of Cancer Multidrug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…An emerging strategy for enhanced CNS delivery is co-administration of such compounds with inhibitors of drug efflux transporters [289][290][291]. First generation Pgp inhibitors include Pgp substrates, such as cyclosporine A and verapamil.…”
Section: Polymeric Inhibitors Of Drug Efflux Systems In Bbbmentioning
confidence: 99%
“…ABC transporter proteins confer drug resistance by actively transporting drugs from the intracellular space to the extracellular space, thereby preventing the interaction of these drugs with their intracellular targets. In the case of ABCB1, expression has been shown to confer resistance to vinca alkaloids, anthracyclines, taxanes, epipodophyllotoxins, and other drugs 9, 10 .…”
Section: Introductionmentioning
confidence: 99%